Robust Control Systems Design Using Matlab - Zainal - Abidin (Universitas Islam Lamongan, 2018)
A steady control system is carried out through optimal design and also using estimation theory, controls designed for process models generally work well, but also sometimes experience failure in a system.The most important thing in the feedback control test model is to improve the robustness performance of the system. Strong control systems make it possible to determine more or less directly the uncertainty of a system, and make it possible to predict possible trade-offs between robustness and closed-loop performance.